Relationship Between Motivation and Family Support with Elderly Visits to Integrated Healthcare Center for Elderly in The Working Area of Asa Village - Murtinawati Murtinawati (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Integrated Healthcare Center for the elderly is a program implemented by the government and run by the Public Health Centre and cadres around the Integrated Healthcare Center for the elderly for health services to the elderly involving several parties such as the government, the elderly, families, community leaders and social organizations. Objective: To determine the relationship between motivation and family support with elderly visits to the Integrated Healthcare Center for the elderly in the working area of ??Kampung Asa. Methods: The design of this study was descriptive correlation with a cross-sectional approach carried out in January 2022. Result and Discussion: Statistical test found the relationship between motivation and elderly visits to the Integrated Healthcare Center for the elderly (pvalue = 0.00). The relationship between family support and elderly visits to the Integrated Healthcare Center for the elderly (pvalue = 0.01). Conclusion: There is a significant relationship between motivation and family support with elderly visits to the Integrated Healthcare Center for the elderly in the working area of ??Kampung Asa